ANALYSIS SYSTEM ON THE USE OF LABOR CONTRACTORS PT. VICO’S INDONESIA - Yudhi Armico; Sunarto Usna Drs. MMSi (Jurnal Sistem Informasi, 2000)
Petroleum industry at this important role in the improvement of the State Capital. Along with that required also potentially Labor. Handling Labor was managed by the company under the Human Resource Department (HRD). System acceptance and usage Labor Contractor PT.VICO’S Indonesia is computerized, so that in the search archives Labor Contractor does not require a long time. All associated with the use of power as the kingdom Contractors, Contractor Manpower data. Contractor Agreement Process Work, Employment Contractors signing period, etc.